What drives binge-watching? An economic theory and analysis of impact factors - Sophia Gänßle; Philipp Kunz-Kaltenhaeuser (Technische Universität Ilmenau, Institut für Volkswirtschaftslehre, 2020)
Behavioral patterns in media consumption are changing. With the upcoming of video-on-demand platforms, so-called "binge-watching" gained broad awareness. To the best of our knowledge, this is the first economic analysis explicitly on binge-watching. We approach the phenomenon by arguing that it follows fundamental patterns of addictive behavior. By applying concepts of rational addiction and behavioral economics, we derive (i) a theoretical understanding of binging-watching behavior and (ii) factors increasing the likelihood of binging, especially with modern technologies and digital media services. The decision to binge depends on individual factors such as the accumulation rate of consumption capital (speed of learning and acquiring knowledge), opportunity costs, and the expected value of consumption. Consumption capital in the form of specific knowledge positively influences marginal utility. Moreover, binge-watching is not specific to online streaming services (video-on-demand), but modern platforms facilitate certain factors which increase the consumers' engagement. Non-linear, self-organized video scheduling and a single narrative (coherent plot) increase the likelihood for con-sumers to binge.
Keywords: D03; D11; D90; L82; Z10; 330; binge watching; video on demand; television; streaming; consumption capital; behavioural economics; media economics